Risks of illness of nursing professors working in in post-graduation courses - Susan Bublitz; Carmem Lúcia Colomé Beck; Rosângela Marion da Silva; Daiane Dal Pai; Silviamar Camponogara (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To identify the risk of illness related to the work context of nurse professors of stricto sensu nursing post-graduation programs of public institutions. Method Mixed study (convergent and parallel) carried out in federal universities in Rio Grande do Sul, with nurse professors, from November 2015 to October 2016. As data collection techniques, the Work Context Assessment Scale and a semi-structured interview were used. The data were analyzed using descriptive statistics and thematic analysis. Results For the quantitative data, it was identified that all factors on the scale were assessed as critical for the risk of illness. The reports complement the quantitative data, and point to work overload, competitiveness, and inadequate infrastructure. Conclusion This study offers subsidies for the implementation of actions aimed at the health of nursing professors and helps in the understanding of the work context, which presents risks for illness.